The solitary wave solutions of the stochastic Heisenberg ferromagnetic spin chain equation using two different analytical methods - Al-Askar, Farah M. (Frontiers in Physics, 2023)
We consider here the stochastic (2 + 1)-dimensional Heisenberg ferromagnetic spin chain equation which is forced by multiplicative Brownian motion in the Stratonovich sense. We utilize the (G /G)-expansion method and mapping method to attain the analytical solutions of the stochastic (2 + 1)-dimensional Heisenberg ferromagnetic chain equation. Various kinds of analytical stochastic solutions, for instance the hyperbolic, elliptic and trigonometric functions, have obtained. Physicists can utilize these solutions to understand a variety of important physical phenomena because magnetic soliton has been categorized as one of the interesting groups of nonlinear excitations representing spin dynamics in semiclassical continuum Heisenberg systems. Moreover, we employ the Matlab tools to plot 3D and 2D graphs for some obtained solutions to address the influence of Brownian motion on these solutions.